Evidence-based education: Objections and future directions - Dekker, Izaak; Meeter, Martijn (Frontiers in Education, 2022)
Over the past two decades, educational policymakers in many countries have favored evidence-based educational programs and interventions. However, evidence-based education has met with growing resistance from educational researchers. This article analyses the objections against evidence-based education and its preference for randomized controlled trials. We conclude that the objections call for adjustments, but do not justify abandoning evidence-based education. Three future directions could make education more evidence-based whilst taking the objections against evidence-based education into account: 1) study local factors, mechanisms and implementation fidelity in randomized controlled trials, 2) utilize and improve the available longitudinal performance data and 3) use integrated interventions and outcome measures.